Nappy hair - Herron, Carolivia; Cepeda, Joe (New York : Dragonfly Books : Distributed by Random House, 1999)
Various people at a backyard picnic offer their comments on a young girl's tightly curled, "nappy" hair.
2.2
K-3
K-3
Book Links (A.L.A.)
Publisher's Weekly
Booklist
Keywords: African Americans -- Fiction; Hair -- Fiction; African Americans -- Fiction; Hair -- Fiction